Consensus guidelines for the management of intracranial ependymoma for low- and middle-income countries - Ahsan Ali Khan; Muhammad Usman Khalid; Mohammad Hamza Bajwa; Izza Tahir; Shahier Paracha; Muhammad Shakir; Bilal Mazhar Qureshi; Naureen Mushtaq; Ahmed Gilani; Pakistan Brain Tumour Consortium: (Authors list at the end of the supplement); et al. (Journal of the Pakistan Medical Association, 2024)
This paper presents comprehensive consensus guidelinesfor the management of intracranial ependymoma,neoplasms arising from ependymal cells in the centralnervous system’s ventricular system, in low- and middleincomecountries (LMICs). Acknowledging the distinctepidemiological patterns of ependymomas, notably theirhigher incidence in paediatric patients, and variablesurvival rates, these guidelines emphasize tailoredmanagement approaches for different age groups. Anexpert panel, comprising specialists in neuro-oncology,convened to address gaps in diagnosis and managementwithin LMICs, considering the varying clinicalpresentation based on tumour size and location.Emphasizing surgical intervention as the cornerstone oftreatment, the guidelines also address challenges such asintraoperative bleeding and tumour location impactingcomplete resection. The role of molecular subgrouping instratifying treatment and predicting prognosis ishighlighted, alongside a careful consideration ofradiotherapy timing, dose, and volume based on riskfactors. Chemotherapy’s role, especially in paediatriccases, is explored. The paper synthesizes current researchand expert opinions, including the need forstandardisation, genetic testing, and exploration of lessinvasive treatment modalities, to address the uniquehealthcare infrastructure challenges in LMICs. Theguidelines also emphasize multidisciplinary teams,aiming to bridge the care gap between high-incomecountries and LMICs, and improve survival rates andquality of life for patients with intracranial ependymoma.This article serves as a valuable resource for clinicians,researchers, and policymakers in Pakistan and beyond,facilitating the development of evidence-based strategiesin diverse healthcare settings. Keywords: Nervous system, genetic, ependymoma,prognosis, ependymoma, surgery, radiotherapy.